Cold cold heart - Hoag, Tami (New York, New York : Dutton, 2015)
Dana Nolan was a TV reporter until she was kidnapped by a notorious serial killer. A year has passed since she defeated her attacker, but Dana is still physically, emotionally, and psychologically scarred by her ordeal. In an attempt to put herself back together after surviving the unthinkable, Dana returns to her hometown.
Keywords: Women television journalists -- Fiction; Victims of crimes -- Fiction; Post-traumatic stress disorder -- Fiction